Rubber tire dust-rice husk pyramidal microwave absorber - Mohd Fareq, Abd. Malek, Dr.; Cheng, Ee Meng, Dr.; O., Nadiah; Nornikman, Hassan; M., Ahmed; M. Z. A., Abd Aziz; A. R., Osman; Soh, Ping Jack; Azremi, Abdullah Al Hadi; A., Hasnain; Mohd Nasir, Taib (EMW Publishing, 2011)
Link to publisher's homepage at http://www.piers.org/